Betel nut chewing associated with increased risk of arterial stiffness. (1st November 2017) - Wei, Yu-Ting; Chou, Yu-Tsung; Yang, Yi-Ching; Chou, Chieh-Ying; Lu, Feng-Hwa; Chang, Chih-Jen; Wu, Jin-Shang
Highlights: Increased arterial stiffness was prevalent in ex- and current chewers. Current betel nut chewing elevates the risk of increased arterial stiffness. Ex-chewers are associated with a higher risk of increased arterial stiffness. Abstract: Background: Betel nut chewing is associated with certain cardiovascular outcomes. Subclinical atherosclerosis may be one link between betel nut chewing and cardiovascular risk. Few studies have examined the association between chewing betel nut and arterial stiffness. The aim of this study was thus to determine the relationship between betel nut chewing and arterial stiffness in a Taiwanese population. Methods: We enrolled 7540 eligible subjects in National Cheng Kung University Hospital from October 2006 to August 2009. The exclusion criteria included history of cerebrovascular events, coronary artery disease, and taking lipid-lowering drugs, antihypertensives, and hypoglycemic agents. Increased arterial stiffness was defined as brachial–ankle pulse wave velocity (baPWV) ≥1400 cm/s. According to their habit of betel nut use, the subjects were categorized into non-, ex-, and current chewers. Results: The prevalence of increased arterial stiffness was 32.7, 43.3, and 43.2% in non-, ex- and current chewers, respectively (p = 0.011). Multiple logistic regression analysis revealed that ex-chewers (odds ratio [OR] 1.69, 95% confidence interval (CI) = 1.08–2.65) and current chewers (OR 2.29, 95% CI = 1.05–4.99) had elevated risks of increased arterial stiffness after adjustment for co-variables. Conclusions: Both ex- and current betel nut chewing were associated with a higher risk of increased arterial stiffness. Stopping betel nut chewing may thus potentially be beneficial to reduce cardiovascular risk, based on the principals of preventive medicine.